Enhancing students' Lampung language pronunciation through audio-visual folk story media - Ariyani, Farida; Widodo, Mulyanto; Yulianti, Dwi (citeus, 2025)
Lampung language is currently experiencing a decline in usage, increasingly being supplanted by other languages. This trend can be attributed to students' waning interest in learning Lampung, which is partly due to the lack of innovative teaching approaches. Additionally, the complexity of Lampung pronunciation, further complicated by the existence of Dialect A and Dialect O, presents another challenge. To address these issues, there is a need for accessible and easy-to-use audio-visual media, particularly those focused on folklore, which can be widely utilized by educators. This study employed a comparative descriptive approach to investigate the impact of folklore-based audio-visual media on students' proficiency in Lampung pronunciation. The research instruments included an observation sheet—designed by the researchers to assess students' pronunciation abilities—and an interview guide to gather insights into students' learning experiences and teachers' perspectives on the instructional process. The findings indicate that the implementation of folklore-based audio-visual media offers significant benefits in enhancing students' pronunciation skills in Lampung. This media aids students in understanding correct pronunciation, boosts learning motivation, increases self-confidence, and improves communication skills. Therefore, teachers are encouraged to select appropriate media tailored to students' proficiency levels and ensure that its use aligns with specific learning objectives to maximize educational outcomes.